Effect of copepod (Apocyclops dengizicus) addition on growth, survival and proximate composition of Macrobrachium rosenbergii postlarvae cultured in brackish water biofloc system. - Hosain, Md. Eilious; Nurul Amin, S. M.; Arshad, Aziz; Kamarudin, Mohd Salleh; Karim, Murni; Shohaimi, Shamarina; Naser, Md. Niamul; Romano, Nicholas (John Wiley & Sons, 2023)
The effects of periodically adding the cyclopoid copepod, Apocyclops dengizicus, (every four days at a rate of 4 individuals/mL) with biofloc technology (BFT-C) was compared with conventional BFT (without copepod) or a clear-water control on the survival, growth, proximate composition, and economics of Macrobrachium rosenbergii postlarvae nursery culture. Water quality and biofloc proximate composition were also measured among treatments. For the BFT, maize starch was applied to achieve C-N ratio 20:1. Triplicate 125 L polyethylene tanks containing 500 postlarvae each (9.40±1.88 mg) were evaluated. Specific growth rate was significantly (p < 0.05) greater in the BFT-C (8.40 ± 0.24 % day-1) than BFT (7.23 ± 0.21 % day-1) and control (7.12 ± 0.42 % day-1) groups. Postlarvae survival was significantly (p < 0.05) increased with the BFT-C (94.46 %) treatment than the BFT (87.33 %) and control (82.60 %). A significantly lower food conversion ratio (1.08) was obtained (p <0.05) in BFT-C than both the BFT (1.73) and control (1.90), possibly due to significantly higher biofloc crude protein and lipid contents in the BFT-C than BFT. Postlarvae whole-body protein and lipid contents were significantly elevated (p <0.05) in BFT-C compared to the BFT and control treatments. Economics of gross return, net return, and benefit-cost ratio were significantly better at BFT-C (p <0.05) than in either BFT or control. This study indicates that copepod additions with BFT enhanced prawn postlarvae survival, growth, whole body protein and lipid, as well as economics, which could augment productivity and sustainability in this industry.